Identifikasi Koi Herpesvirus pada Dosis yang Berbeda dengan Metode Imunohistokimia Streptavidin Biotin pada Ikan Nila (Oreochromis niloticus) [Identification of Koi Herpes Virus At Different Dose with Streptavidin Biotin Methods Immunohistochemistry on Tilapia (Oreochromis niloticus)] - Hari Suprapto; Faricha Risma Nurani; Suwarno Suwarno (Jurnal Ilmiah Perikanan dan Kelautan, 2014)
Abstract KHV is a viral disease in goldfish and Koi Fish (Cyprinus carpio) is a highly contagious, infecting all ages or sizes of fish and aquaculture systems. This disease results in mortality between 80% - 100% of the total fish population, with an incubation period of between 1-7 days. KHV infection triggered by a drop in ambient temperature so it is referred to as a virus that attacks when cold (a cold virus). The disease attacks the temperature range of 18-28 ° C and can cause death. This virus attacks can occur at any age of the fish ranging in size from the seed to the parent. The most prominent clinical symptoms due to KHV infection is the sudden death 1-2 days after infection. Other clinical symptoms are necrosis of the gills, sunken eyes, bleeding at the gills, hemorraghe, excess mucus production in the body, and secondary bacterial infections or parasitic infestations. Streptavidin biotin immunohistochemical method was applied to the study of cells and tissues by staining imunostaining. Technique of determining the existence of (location) antigen (target protein) in tissue using antigen-antibody reaction that begins with histotenik procedure is the procedure of making tissue sections (histology). This method has high sensitivity and fast so that it can be applied to the detection of KHV antigen in tissues of fish Tilapia (Orechromis niloticus). This study aims to determine the presence of KHV antigen in tilapia gills after infection. The method used in this study is the experimental method. Dose of virus titer used was 1 ID50, ID50 10, 100 ID50, ID50 1000. The results showed that the Streptavidin Biotin immunohistochemical examination imunopatologi able to detect KHV virus Ag in the gill tissue of tilapia (Oreochromis niloticus) were infected with different doses. In all treatments showed on all the gills are KHV antigen is indicated by the presence of a golden brown color on the gill epithelium. Advised Streptavidin biotin immunohistochemistry test was applied to the detection of the presence or absence of fish-carp KHV carrier as a routine control program and control, including the prevention and outbreak of KHV in Indonesia, because of KHV were attacked in tilapia was persistent and did not show clinical symptoms